PENGARUH CAR, NPL, LDR, DPK, BOPO DAN SIZE TERHADAP ROA (RETURN ON ASSETS) PADA BANK UMUM GO PUBLIC PERIODE 2005-2012 - Stefani Gusti Anggra Murti, 12.05.52.0235; Aini, Nur (Students Journal of Accounting and Banking, 2014)
Purpose of this research is to know the influence of variables CAR, NPL, LDR, DPK, BOPO, and SIZE to ROA. Research period that used in this research is start from 2005 until 2012, with reasearch object are common bank that have been go public in Bursa Efek Indonesia. Chooshen sample that used in this research are 198 datas, with 8 years research period. Model that used in this research is double linear regression analisys, with IBM SPSS 20 programme and use 5% level signification. Result of this research show that simultancy independent variables CAR, NPL, LDR, DPK, BOPO and SIZE have significant influent to ROA. While, partially CAR and SIZE have negative influent and significant to ROA. Evenwhile BOPO has negatif influent and significant to ROA. Other variables LDR has positif influent but not significant to ROA. So do NPL and DPK have negatif influent but not significant to ROA. Keywords: Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Loan to Deposit Ratio (LDR), Dana Pihak KetigaÂ  (DPK), Biaya Operasional Pendapatan OperasionalÂ  (BOPO), Besaran Perusahaan (SIZE), Return On Asset (ROA)